P.8: Trap States in Amorphous In‐Sn‐Zn‐O Thin‐Film Transistors Analyzed Using Dependence on Channel Thickness. Issue 1 (1st July 2013) - Matsuda, Tokiyoshi; Kimura, Mutsumi; Jiang, Jingxin; Wang, Dapeng; Furuta, Mamoru; Kasami, Masashi; Tomai, Shigekazu; Yano, Koki
Abstract: Trap states in α‐ITZO TFTs are analyzed using the dependences of the trap densities on the channel thickness. Utilizing extraction methods of trap densities in the film, at the front and back interfaces it is suggested that the trap states are not distributed in the film but localized at the interface